Proteolytic cleavage of membrane proteins by membrane type‐1 MMP regulates cancer malignant progression. Issue 2 (24th November 2022) - Ikeda, Kazuki; Kaneko, Ryo; Tsukamoto, Eiki; Funahashi, Nobuaki; Koshikawa, Naohiko
Abstract: Strategies to develop cancer therapies using inhibitors that target matrix metalloproteinases (MMPs), particularly membrane type‐1 MMP (MT1‐MMP), have failed. This is predominantly attributed to the specificity of MMP inhibitors and numerous functions of MMPs; therefore, targeting substrates with such broad specificity can lead to off‐target effects. Thus, new drug development for cancer therapeutics should focus on the ability of MT1‐MMP to break down substrates, such as functional cell membrane proteins, to regulate the functions of these proteins that promote tumor malignancy. In this review, we discuss the mechanism by which proteolysis of cell surface proteins by MT1‐MMP promotes progression of malignant tumor cells. In addition, we discuss the two protein fragments generated by limited cleavage of erythropoietin‐producing hepatoma receptor tyrosine kinase A2 (EphA2‐NF, ‐CF), which represent a promising basis for developing new cancer therapies and diagnostic techniques. Abstract : Cell surface proteolysis by MT1‐MMP promotes malignant progression of tumor cells and may be a diagnostic and theputic ratget for cancers.